2011
DOI: 10.3324/haematol.2011.041434
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors underlying the risk of bortezomib induced peripheral neuropathy in multiple myeloma patients

Abstract: In addition, a dataset based on the patients from the HOVON-65/GMMG-HD4 trial were used as a validation set.11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 25 publications
(27 reference statements)
2
26
0
Order By: Relevance
“…The present pharmacogenomics GWA study also confirmed the modest association of the rs619824 genotype with BiPN ( P =0.043) previously identified by Corthals and colleagues (8). Although there has been no overlap with a previous study on late-onset of BiPN associated variants reported by Broyl and colleagues (10) as shown in Supplementary Table S4.…”
Section: Resultssupporting
confidence: 92%
“…The present pharmacogenomics GWA study also confirmed the modest association of the rs619824 genotype with BiPN ( P =0.043) previously identified by Corthals and colleagues (8). Although there has been no overlap with a previous study on late-onset of BiPN associated variants reported by Broyl and colleagues (10) as shown in Supplementary Table S4.…”
Section: Resultssupporting
confidence: 92%
“…Bortezomib inhibits the proteasome within PCs, resulting in inability to degrade misfolded proteins, which eventually leads to apoptosis. While Bortezomib has shown promise in reducing disease activity and decreasing autoAbs concentrations while increasing complement levels [71], this drug has been associated with serious neurotoxicity [73]. …”
Section: Therapiesmentioning
confidence: 99%
“…We initiated this study to determine whether SC administration of bortezomib could decrease the incidence of Pn in Korean patients. Genetic factors, including single-nucleotide polymorphisms (SnPs) in CYP families, CDKn1B, tnFα, IKBKaP, and the CtLa4 gene [11], are known to be associated with BIPn. the frequency of some SnPs, such as rs11466155 and rs228851, varies across ethnic groups.…”
Section: Discussionmentioning
confidence: 99%